Syntax and morphology of Baniswola Pashto: investigating universal and dialectal variations - Afaq Khan; Tahir Saleem; Arshad Ali Khan; Summiya Azam (Cogent Arts & Humanities)
This study investigates the syntactic and morphological structures of Baniswola Pashto, a dialect spoken in Bannu, Pakistan, through Chomsky’s Minimalist Program (MP). It examines nouns, verbs, adjectives, determiners, pronouns, and complementizers using syntactic tests to analyze agreement mechanisms, feature checking, and clause embedding. Findings reveal distinct gender, number, and case agreement patterns in nouns and adjectives, alongside unique syntactic flexibility in determiners like daɣa (‘this’) and aɣa (‘that’). Verbs exhibit inflectional complexity, marking tense, aspect, and subject-verb agreement, while complementizers like ʧe (‘that’) and ka (‘if’) function as critical phase heads for embedding clauses and ensuring syntactic coherence. The research highlights the dialect’s alignment with universal syntactic principles, such as feature valuation and Merge, while identifying language-specific variations challenging certain MP assumptions, especially in multifunctional determiners and pronouns. Comparative analyses with Indo-Iranian languages accentuate shared traits, yet Baniswola Pashto introduces distinct morphosyntactic features, enriching cross-linguistic understanding. This work documents a lesser-studied Pashto dialect, offering theoretical insights into minimalist syntax and typological studies. The findings expand syntactic research on Pashto, providing a foundation for further exploration of linguistic diversity and grammatical frameworks in under-documented languages while addressing the dialect’s contribution to the broader Indo-Iranian linguistic family.